The content of the active layer external surface resistance to weathering/Aktyviojo išorinio paviršiaus patvarumo aplinkos poveikiams turinys (kiekis) - Barkauskas, Vytautas (Journal of Civil Engineering and Management, 2001)
The external surfaces of finish wear and disintegrate under weathering conditions. It is known that the layer in which the amplitude of temperature and surface moisture decreases twice is intensively affected. When investigating the surface durability, it would be useful to call this layer an active layer. Its durability is proportional to the square of the layer thickness and to the ratio of inner energy (meant for resistantial influence). Usually the dispersion of physical and mechanical properties in materials and samples is calculated by statistic methods. Analytically it is possible to assume that any product or sample consists of many hypothetic microvolumes demonstrating certain physical and mechanical properties. According to our tests carried out during years, the dispersion of these microvolumes is similar to that of products or samples and may be estimated by statistic curves.Article in Lithuanian.First Published Online: 30 Jul 2012